Telemedicine and its impact on public health in the United States: a contemporary review - Victor Ezeamii; Natalie O O Doherty; Chinwe Olivia Ayozie; Alexander Samuel Figueroa; Okelue Edwards Okobi (The Egyptian Journal of Internal Medicine)
Abstract Background The review paper explores the evolution, benefits, and challenges of telemedicine within the U.S. healthcare system. Originally developed to address the needs of remote and underserved populations, telemedicine has seen significant expansion, particularly during the COVID-19 pandemic. Method This review synthesizes recent literature to assess telemedicine’s impact on healthcare access, quality, and equity. Findings The findings indicate that telemedicine has significantly enhanced healthcare access, particularly for chronic disease management and mental health services, but also reveal challenges such as regulatory barriers, technological limitations, and disparities in access, especially in rural areas. Additionally, the review highlights the need for a unified national telemedicine policy, robust data security measures, and targeted interventions to ensure equitable access. Conclusion The paper concludes that while telemedicine offers transformative potential, realizing its full benefits requires addressing these systemic challenges through collaboration among policymakers, healthcare providers, and researchers.